Pharmacogenetics of CYP2D6 and tamoxifen therapy: Light at the end of the tunnel?. (May 2016) - Del Re, M.; Citi, V.; Crucitta, S.; Rofi, E.; Belcari, F.; van Schaik, R.H.; Danesi, R.
Graphical abstract: Abstract: The clinical usefulness of assessing the enzymatic activity of CYPD6 in patients taking tamoxifen had been longly debated. In favour of preemptive evaluation of phenotypic profile of patients is the strong pharmacologic rationale, being that the formation of endoxifen, the major and clinically most important metabolite of tamoxifen, is largely dependent on the activity of CYP2D6. This enzyme is highly polymorphic for which the activity is largely depending on genetics, but that can also be inhibited by a number of drugs, i.e. antidepressants, which are frequently used in patients with cancer. Unfortunately, the clinical trials that have been published in the last years are contradicting each other on the association between CYP2D6 and significant clinical endpoints, and for this reason CYP2D6 genotyping is at present not generally recommended. Despite this, the CYP2D6 genotyping test for tamoxifen is available in many laboratories and it may still be an appropriate test to use it in specific cases.